Effects of naphthylmethyl isoquinoline on contraction and calcium flux of rabbit vascular strips in vitro - Zhu Wei-Zhong; Yang Yu-Lin (Acta Pharmacologica Sinica; Vol 13, No 2 (March 1992): Acta Pharmacologica Sinica, 2016)
Naphthylmethyl isoquinoline (NI) 1-30 mumol.L-1 inhibited the contraction of rabbit vascular smooth muscle in vitro induced by KCl, CaCl2, and norepinephrine (NE). NI 0.3-30 mumol.L-1 blocked 45Ca2+ influx process in vascular smooth muscle of aorta, mesenteric and femoral arteries by addition of KCl and NE. NI 3-10 mumol.L-1 had no effect on 45Ca2+ efflux from aorta at resting state. These results suggest that the relaxing effect of NI on rabbit blood vessels may be relevant to the inhibition of Ca2+ influx into vascular smooth muscle.